Bats in a changing landscape: Linking occupancy and traits of a diverse montane bat community to fire regime. Issue 9 (12th April 2019) - Blakey, Rachel V.; Webb, Elisabeth B.; Kesler, Dylan C.; Siegel, Rodney B.; Corcoran, Derek; Johnson, Matthew
Abstract: Wildfires are increasing in incidence and severity across coniferous forests of the western United States, leading to changes in forest structure and wildlife habitats. Knowledge of how species respond to fire‐driven habitat changes in these landscapes is limited and generally disconnected from our understanding of adaptations that underpin responses to fire. We aimed to investigate drivers of occupancy of a diverse bat community in a fire‐altered landscape, while identifying functional traits that underpinned these relationships. We recorded bats acoustically at 83 sites ( n  = 249 recording nights) across the Plumas National Forest in the northern Sierra Nevada over 3 summers (2015–2017). We investigated relationships between fire regime, physiographic variables, forest structure and probability of bat occupancy for nine frequently detected species. We used fourth‐corner regression and RLQ analysis to identify ecomorphological traits driving species–environment relationships across 17 bat species. Traits included body mass; call frequency, bandwidth, and duration; and foraging strategy based on vegetation structure (open, edge, or clutter). Relationships between bat traits and fire regime were underpinned by adaptations to diverse forest structure. Bats with traits adapting them to foraging in open habitats, including emitting longer duration and narrow bandwidth calls, were associated with higher severity and more frequent fires, whereas bats with traits consistent with clutter tolerance were negatively associated with fire frequency and burn severity. Relationships between edge‐adapted bat species and fire were variable and may be influenced by prey preference or habitat configuration at a landscape scale. Predicted increases in fire frequency and severity in western US coniferous forests are likely to shift dominance in the bat community to open‐adapted species and those able to exploit postfire resource pulses (aquatic insects, beetles, and snags). Managing for pyrodiversity within the western United States is likely important for maintaining bat community diversity, as well as diversity of other biotic communities. Abstract : Wildfires are increasing in incidence and severity across the western United States, but we know little about the adaptations that underpin species relationships with burned habitats. We investigated relationships between bat occupancy, forest structure, and fire regime and identified ecomorphological traits driving these species–environment relationships, in a community of 17 bats species in the fire‐prone Sierra Nevada forest of the western United States. We found that bats adapted to foraging in open habitats and emitting longer duration and narrow bandwidth calls were associated with higher severity and more frequent fires, and therefore predicted increases in fire frequency and severity for the western United States may lead to dominance of these species in forests of the region.